Effects of paraoxonase 1 gene polymorphisms on heart diseases: Systematic review and meta-analysis of 64 case-control studies. Issue 44 (November 2016) - Hernández-Díaz, Yazmín; Tovilla-Zárate, Carlos Alfonso; Juárez-Rojop, Isela Esther; González-Castro, Thelma Beatriz; Rodríguez-Pérez, Candelario; López-Narváez, María Lilia; Rodríguez-Pérez, José Manuel; Cámara-Álvarez, José Francisco
Abstract: Background: Associations between paraoxonase 1 ( PON1 ) gene polymorphisms and heart diseases (HD) risk remain inconsistent. In order to obtain address this issue we performed a meta-analysis to assess the association between the L55M and Q192R polymorphisms of PON1 gene and heart diseases risk. Methods: Relevant studies were enrolled by searching databases systematically. Odds ratios (ORs) with 95% confidence intervals (CIs) were used to calculate the strength of association. Subgroup analyses were conducted for diagnostic and ethnicity. The heterogeneity among each of the studies was calculated by using Cochran Qtest and the inconsistency index ( I 2 ), and Begg's funnel plot and Egger's tests were performed to evaluate publication bias. Result: Sixty four studies involving a total of 19, 715 cases and 33, 397 controls were included in this meta-analysis. We found that the L55M polymorphism showed a significant association with heart diseases in Europeans (OR 1.44, 95%CI 1.33–1.56) and Asians (OR 1.18, 95%CI 1.03–1.35). This meta-analysis also showed a protective association of Q192R polymorphism with HD in Asian (OR 0.49, 95%CI 0.37–0.66) and African populations (OR 0.67, 95%CI 0.53–0.84). The 192R allele significantly decreased the risk of myocardial infarction (OR 0.75, 95%CI 0.57–0.99) and coronary artery disease (OR 0.91, 95%CI 0.84–0.98); however, individuals with 192Q allele had a markedly increased risk of coronary artery disease development (OR 1.38, 95%CI 1.22–1.56). Conclusion: This study demonstrated that the genetic risk for heart diseases is associated with the PON1 gene polymorphisms. L55M polymorphism is a risk factor and Q192R polymorphism is protective in certain populations. It is worth noting that the 192Q allele may be a risk factor to develop coronary artery disease.